Variables monitoring for the two stroke engine using computer interfacing technique / Khairulnizam Ngadimon and Ahmad Fikri Mohamed Omar - Ngadimon, Khairulnizam; Mohamed Omar, Ahmad Fikri (2000)
Studying of the performance and perfoming the analysis of an internal combustion engine is a quite complicated work. We need to know many variables through which we will be able to investigate the behaviour of the engine. Such variables are temperature, pressure, speed, torque and exhaust gases temperature etc. The readings need to be taken many times over a short time. A previous phase of this work was done to make the measurement for the sake of realisation of the radical combustion. However the main problem faced is detecting and measuring of the variables was an obstacle, when it is needed to investigate the behaviour of those variables within a short duration of time. For example, a two - stroke engine that runs at 3600rpm (or 60rev/s) will undergoes Top Dead Centre (TDC) for every 0.0167 seconds. It is totally impossible for human to record the pressure and temperature at this short interval of time. In this work the main task is to overcome the above problem, by the means of providing the proper interfacing between the engine and the Personal Computer (PC), which help for providing high accuray of measurement as well as data data acquisition for further analysis.